2012
DOI: 10.1038/nphoton.2012.188
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Towards high-speed imaging of infrared photons with bio-inspired nanoarchitectures

Abstract: In the version of this Article originally published, the measured temperature difference ΔT was at the detector plane, whereas the definition of noise-equivalent temperature difference (NETD) in equation (2) requires ΔT to be a thermal scene temperature difference. Thus, the NETD terminology in equation (2) has now been replaced with temperature sensitivity (TS). This error has been corrected in the HTML and PDF versions of the Article. CORRIGENDUM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Biological strategies for light manipulation have already been successfully implemented in nanophotonic devices for applications in chemically selective vapor sensing, pH determination, infrared imaging, surface-enhanced Raman spectroscopy-based chemical analysis, and localized heating from infrared absorption (29)(30)(31)(32)(33)(34). The rich and tunable optical signature of our hierarchical bioinspired diffraction-based photonic material platform could provide a basis for novel developments in biosensing (35)(36)(37), efficient light management in photovoltaic systems (38)(39)(40), enhanced light extraction and radiation profile shaping in lightemitting diodes (41)(42)(43), and optically variable devices in consumer product design and anticounterfeiting (44)(45)(46).…”
Section: Significancementioning
confidence: 99%
“…Biological strategies for light manipulation have already been successfully implemented in nanophotonic devices for applications in chemically selective vapor sensing, pH determination, infrared imaging, surface-enhanced Raman spectroscopy-based chemical analysis, and localized heating from infrared absorption (29)(30)(31)(32)(33)(34). The rich and tunable optical signature of our hierarchical bioinspired diffraction-based photonic material platform could provide a basis for novel developments in biosensing (35)(36)(37), efficient light management in photovoltaic systems (38)(39)(40), enhanced light extraction and radiation profile shaping in lightemitting diodes (41)(42)(43), and optically variable devices in consumer product design and anticounterfeiting (44)(45)(46).…”
Section: Significancementioning
confidence: 99%
“…A TEM image of the cross-section of the Morpho sulkowskyi ground scale reveal the "Christmas tree" like structure responsible for the famous blue iridescence. Reproduced from Pris et al [10]. (c) Schematics of the structures and dimensions (all units in nm) used in this study for simulation and fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)) and developed fabrication methods to replicate their design for various applications [7][8][9][10][11]. Potyrailo et al [9], for example, revealed that the optical response of the nano-scale structures of the Morpho butterfly changes for different vapors.…”
Section: Introductionmentioning
confidence: 99%
“…The colour reflectance response of Morpho wings also offers sensitivity to mid-wavelength infrared radiation. Thermally-induced reflectivity changes give rise to detectable visible-range colour shifts [127]. While these are interesting avenues of bioinspired exploitation, they appear to serve no discernable biological function to the animal itself, unlike for example, the humidity-induced colour change observed in Dynastes hercules beetles, that is providing new inspiration for humidity sensing applications [128][129][130].…”
Section: Morpho-related Bioinspired Applicationsmentioning
confidence: 99%